REVITALIZATION OF THE MODERN MOVEMENT IN ISLAM AS A FOUNDATION FOR EDUCATIONAL RENEWAL IN THE DIGITAL ERA - Hasanah, Siti Uswatun; Akasyah, Dudi; Hardjadinata, `Hardjadinata; Murodi, Murodi; Luthfi, Atabik (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The 21st century is marked by a wave of major changes in various aspects of life, including in the field of education. Amid the rapid development of digital technology, Islamic education faces challenges as well as great opportunities to make relevant and transformative reforms. This article discusses the importance of revitalizing the modern movement in Islam as a foundation in the process of educational reform, especially in responding to the needs of the digital generation. The modern movement in Islam, which since the early 19th century until now has emphasized rationality, renewal of thought, ijtihad, and adaptation to the development of the times, has a strategic role in encouraging a more open, inclusive, and future-oriented education system. Through a descriptive qualitative approach and literature review, this article examines how the basic principles of the modern movement can be used as a basis for developing an Islamic education model that is responsive to the digital era, without losing the values ​​of Islamic spirituality and ethics. The results of the study show that the synergy between modern Islamic thought and digital innovation can produce an Islamic education system that is progressive, adaptive, and deeply rooted in the tradition of Islamic knowledge. Thus, the revitalization of the modern movement in Islam is not only a historical discourse, but also a strategic path in preparing a generation of Muslims who are intelligent, critical, and globally competitive in the midst of the world's digitalization